Exploring the Impact of Digital Devices on Social Development in Young Children - Regil Sriandila; Dadan Suryana (STAI Hubbulwathan Duri, 2023)
This study aims to describe the gadget phenomenon in early childhood social development. Technological developments, especially gadgets, have penetrated and even made early childhood consumers of gadgets. Despite the fact that gadgets are electronic tools for adult conversation, not toddlers. However, parents give gadgets in early childhood as a way to calm children. To see the social development of early childhood while using gadgets, the researchers used the case studies research method. Data collection was carried out by observation and interviews. The results of the study show that parents should consider what image they convey to their children and how they communicate responsible smartphone consumption. So that gadgets as technological advances can still be used, but the social development of early childhood as social beings is not disturbed by the preoccupation with using gadgets.